Love of Life Model: role of psychological well-being, depression, somatic health, and spiritual health. Issue 2 (7th February 2021) - Dadfar, Mahboubeh; Gunn III, John F.; Lester, David; Abdel-Khalek, Ahmed M.
ABSTRACT: The aims of the present study were (a) to develop a Love of Life Model for psychiatric outpatients, (b) to explore correlations for love of life with psychological well-being, depression, somatic health, and spiritual health, and (c) to explore gender-related differences. A sample of 250 Iranian psychiatric outpatients responded to the Love of Life Scale, World Health Organization-Five Well-Being Index, Patient Health Questionnaire-9, Patient Health Questionnaire-15, and Spiritual Well-Being Scale. The regression analysis was successful in predicting Love of Life scores with spiritual health and psychological well-being as significant predictors of love of life, indicating the importance of paying attention to these two components and strengthening them in psychiatric outpatients. Gender-related differences were not significant. The results support the development and practice of love of life-focused therapy for the treatment of psychiatric outpatients, with a concentration on two issues: creating enjoyable positive emotions and changing the patient's focus toward a positive outlook on life.